Effective noise removal technique for enhancement of the X-ray image / Azman Mohamed - Mohamed, Azman (2005)
The noise removal is an important aspect of image processing, because the human visual System is very sensitive to the high amplitude of noise signals, thus noise in an image can result in a subjective loss of information. There are a lot of methods for noise removal like the Median, Mean, Gaussian or other filter. But there are only few measuring methods for the quality of a smoothed image. In most cases the developed filters are tested on standard images. On the other hand it is difficult to decide, which filter should be used for a given image with noise introduced to it. In this paper two methods for noise removal are introduced which are mean and median filtering in order examine important features for an automatic detection of adequate smoothing operators for a given noisy X-ray image. This paper tries to find the most suhable methods for noise removal and using the Signal-to-Noise Ratio to measure the noise.